Integrating Social Skills into Higher Education Curricula: Preparing Students for Industry 5.0 - Moh Badrut Tamam (Program Studi Pendidikan IPS Unesa, 2026)
Study explores the evolving nature of employability skills, particularly focusing on the integration of social skills within higher education curricula to enhance graduates' competitiveness in an increasingly dynamic labor market. Driven by the rise of the Industry 5.0 paradigm, which emphasizes human-centric collaboration with intelligent machines, this research highlights the growing demand for workers who not only possess technical expertise but also strong interpersonal competencies. Using bibliometric analysis, the study examines publications from 2016 to 2025, revealing a significant surge in research on employability skills, particularly after 2021. The findings underscore a notable shift in higher education, with increasing emphasis on the development of both technical and social skills, such as communication, leadership, and teamwork, which are critical for career success. Furthermore, this research identifies the pivotal role of work-integrated learning in preparing graduates for the workforce, suggesting that curricula must adapt to incorporate these practical experiences. The study contributes valuable insights for policymakers and educators, urging closer collaboration between the educational and industrial sectors to ensure curricula align with labor market demands. By fostering the integration of social skills alongside technical training, higher education institutions can better equip graduates to meet the challenges of the global workforce.